2022
DOI: 10.1159/000526962
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Health-Related Quality of Life in Patients with Metastatic Urothelial Carcinoma Undergoing Immunotherapy with Pembrolizumab: Symptom Burden Can Predict Survival

Abstract: <b><i>Introduction:</i></b> Despite the fact that guidelines recommend monitoring of quality of life during all phases of treatment in urothelial carcinoma, prospective data about health-related quality of life (HRQoL) in metastatic urothelial carcinoma undergoing immunotherapy are sparse. Consequently, we performed a prospective clinical pilot study about HRQoL using the Functional Assessment of Cancer Therapy – Immune Checkpoint Modulator (FACT-ICM) questionnaire. <b><i>Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Real‐world studies conducted in the United States of America before the availability of most novel agents, found that patients who did not receive treatment after discontinuing first‐ or second‐line PD‐1/L1 inhibitor therapy had low overall survival, substantial resource use, economic burden, and QoL impairment 32,33 . Together, these findings highlight the importance of increasing access to effective later treatment lines, managing symptom burden, which can affect outcomes, and addressing QoL in patients with la/mUC 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐world studies conducted in the United States of America before the availability of most novel agents, found that patients who did not receive treatment after discontinuing first‐ or second‐line PD‐1/L1 inhibitor therapy had low overall survival, substantial resource use, economic burden, and QoL impairment 32,33 . Together, these findings highlight the importance of increasing access to effective later treatment lines, managing symptom burden, which can affect outcomes, and addressing QoL in patients with la/mUC 34 …”
Section: Discussionmentioning
confidence: 99%
“…32,33 Together, these findings highlight the importance of increasing access to effective later treatment lines, managing symptom burden, which can affect outcomes, and addressing QoL in patients with la/mUC. 34…”
Section: Discussionmentioning
confidence: 99%